Community Empowerment Through the Application of the Story Method in Fostering Children's Morals at the Yasin Mahbub Prayer Room, Sukadadi Village - Meli Wati; Didik Himmawan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
Morals are a person's behavior or behavior that is carried out consciously and gives birth to good deeds. Morals are the soul of the Islamic religion so that appropriate methods are needed in forming and fostering them. The Qur'an gives a hint that stories have an important role in shaping and developing morals. This coaching is carried out using the story method that happened to former people such as the stories of prophets and apostles and companions of the prophet which are also found in the Al-Qur'an. The Al-Qur'an also perpetuates many important and useful stories that occurred in the history of ancient people by living in His Word to make humans always do good and imitate these stories so that they are used as guidelines and examples for their lives. If his view of life is centered on the principles of the Qur'anic view, then the morals that arise are the morals of the Qur'an. And in the Qur'an contains a lot of history that can be used as a role model for humanity, especially Muslims to be a guide as well as guidance in dealing with life problems